2022
DOI: 10.1007/s40519-022-01397-4
|View full text |Cite
|
Sign up to set email alerts
|

Mediation models of anxiety and depression between temperament and drive for thinness and body dissatisfaction in anorexia nervosa

Abstract: Purpose Anorexia nervosa (AN) is a life-threatening condition in which temperament, anxiety, depression, and core AN body-related psychopathology (drive for thinness, DT, and body dissatisfaction, BD) are intertwined. This relationship has not been to date disentangled; therefore, we performed a multiple mediation analysis aiming to quantify the effect of each component. Methods An innovative multiple mediation statistical method has been applied to data f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 73 publications
1
3
0
Order By: Relevance
“…As we highlighted, perfectionism has displayed a direct correlation with the drive for thinness and the anxious temperament. This evidence is further intriguing as in previous studies, the anxious temperament has been shown to have a significant unmediated effect on the drive for thinness and body dissatisfaction (Jérolon et al, 2022) and on the eating psychopathology and BMI (Marzola et al, 2017(Marzola et al, , 2020. Many possible explanations could be behind these data.…”
Section: Multivariate Regressionsupporting
confidence: 61%
See 2 more Smart Citations
“…As we highlighted, perfectionism has displayed a direct correlation with the drive for thinness and the anxious temperament. This evidence is further intriguing as in previous studies, the anxious temperament has been shown to have a significant unmediated effect on the drive for thinness and body dissatisfaction (Jérolon et al, 2022) and on the eating psychopathology and BMI (Marzola et al, 2017(Marzola et al, , 2020. Many possible explanations could be behind these data.…”
Section: Multivariate Regressionsupporting
confidence: 61%
“…To the best of our knowledge, literature did not address this association. We found that the high‐perfectionism group displayed depressive, cyclothymic, irritable and anxious temperaments, which are the temperaments with the highest impact on eating‐related symptoms, especially regarding the anxious and depressive one (Jérolon et al, 2022; Marzola et al, 2020). The clarification of the relationship between perfectionism and affectivity could be relevant in the treatment of patients with AN.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…An individual who feels unable to initiate any kind of action, suffering from depressive symptoms, is very different from an individual who suffers from a high level of impulsivity. Therefore, subjective experience of the sense of agency combined with temperamental and symptomatic aspects may be both important contributors to the experiential aspects of the body image disturbance in EDs 55 . In terms of states that can be related to EDs, we measured in the present study depression, anxiety, dissociation, non-suicidal self-injurious behaviours, while in terms of traits, we analysed impulsivity, emotion dysregulation, identity representation, and history of traumatic experiences.…”
Section: Introductionmentioning
confidence: 99%